A Phenomenological Study of Ethnic Entrepreneurship and Business Sustainability among Young MSME Entrepreneurs - Hastin Umi Anisah; Aufa Habibie; Muhammad Afrimal Firdaus (At-Taradhi Jurnal Studi Ekonomi, 2025)
This study aims to provide a comprehensive understanding of the implementation of ethnic entrepreneurship among young MSME entrepreneurs in Banjarmasin City. Specifically, it seeks to explore the phenomenon of ethnic entrepreneurship and to examine whether its application influences the sustainability of young entrepreneurs’ MSMEs in the city. Data were collected from five key informants selected through a snowball sampling technique. The research employed passive participant observation, semi-structured interviews, and both open- and closed-ended questionnaires as data collection instruments. Emphasizing an emic perspective, the study prioritized the perceptions and experiences of the key informants. A phenomenological analytical approach, as proposed by Miles and Huberman, was utilized to interpret the data. The findings reveal that ethnic entrepreneurship significantly contributes to the sustainability of young entrepreneurs’ MSMEs in Banjarmasin City.   Keywords:Ethnic entrepreneurship, Sustainability, Young entrepreneurs, MSMEs   How to Cite:Anisah, H. U., Habibie, A., and Firdaus, M.A. “A Phenomenological Perspective on Ethnic Entrepreneurship and Sustainability of Young Entrepreneurs MSMEs.” At-Taradhi: Journal of Economic Studies 16, no. 2 (2025): 125-136   This study aims to provide a comprehensive understanding of the implementation of ethnic entrepreneurship among young MSME entrepreneurs in Banjarmasin City. Specifically, it seeks to explore the phenomenon of ethnic entrepreneurship and to examine whether its application influences the sustainability of young entrepreneurs’ MSMEs in the city. Data were collected from five key informants selected through a snowball sampling technique. The research employed passive participant observation, semi-structured interviews, and both open- and closed-ended questionnaires as data collection instruments. Emphasizing an emic perspective, the study prioritized the perceptions and experiences of the key informants. A phenomenological analytical approach, as proposed by Miles and Huberman, was utilized to interpret the data. The findings reveal that ethnic entrepreneurship significantly contributes to the sustainability of young entrepreneurs’ MSMEs in Banjarmasin City.   Penelitian ini bertujuan untuk memberikan pemahaman komprehensif mengenai implementasi kewirausahaan etnis di kalangan wirausaha muda pelaku UMKM di Kota Banjarmasin. Secara khusus, penelitian ini berupaya mengkaji fenomena kewirausahaan etnis serta menelaah apakah penerapannya berpengaruh terhadap keberlanjutan UMKM yang dijalankan oleh wirausaha muda di kota tersebut. Data dikumpulkan dari lima informan kunci yang dipilih melalui teknik snowball sampling. Proses pengumpulan data menggunakan observasi partisipan pasif, wawancara semi-terstruktur, serta kuesioner terbuka dan tertutup. Dengan menekankan perspektif emik, penelitian ini memprioritaskan persepsi dan pengalaman langsung para informan kunci. Analisis data dilakukan menggunakan pendekatan fenomenologis sebagaimana dikembangkan oleh Miles dan Huberman. Temuan penelitian menunjukkan bahwa kewirausahaan etnis berkontribusi secara signifikan terhadap keberlanjutan UMKM para wirausaha muda di Kota Banjarmasin.